2017
DOI: 10.1136/bcr-2017-221541
|View full text |Cite
|
Sign up to set email alerts
|

Management challenges of late presentation Dacron patch infection after carotid endarterectomy

Abstract: An 83-year-old man presented 4 years after right carotid endarterectomy (CEA) with an infection of his prosthetic Dacron patch. Initial scans (CT angiogram and whole body labelled white cell scan) were clear with no infection or collection noted. Systemically, the patient presented well with no recorded fevers. With an occluded left internal carotid artery and severely stenosed vertebral arteries, surgery presented a high risk of major stroke due to the lack collateral supply and this was discussed extensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The most performed intervention in the case of carotid patch infection is complete patch removal and reconstruction. 4 This strategy is probably the gold standard for the majority of patients. Options for reconstruction include primary closure, autologous vein patch, and vein or native artery bypass.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most performed intervention in the case of carotid patch infection is complete patch removal and reconstruction. 4 This strategy is probably the gold standard for the majority of patients. Options for reconstruction include primary closure, autologous vein patch, and vein or native artery bypass.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, this option has been reported in 26 cases (20% of the patch infections). 4 Most of them were included in a single series of carotid patch infections where the authors reported the patch preservation in 17 of 25 patients. Interestingly, only one of them presented a draining sinus, whereas most of them presented more serious symptoms, even though they found similar long-term results with patch preservation and patch excision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations